Comparison of non-invasive haemodynamic monitors of stress response to endo-tracheal intubation with perfusion index in patients undergoing elective surgery - Lama Moktan, Sushila; Karki, Manan (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Laryngoscopy and intubation is always associated with a short term reflex sympathetic pressor response. The perfusion index is an indirect, non-invasive, and continuous measure of peripheral perfusion by pulse oximeter which can detect the stress response to intubation similar to heart rate, systolic blood pressure and diastolic blood pressure.Methods: This prospective observational study enrolled sixty-five normotensive patients of American society of anesthesiologists physical status grade I and II scheduled for elective surgery under general anaesthesia. Tracheal intubation was performed after induction with intravenous fentanyl, propofol and vecuronium. Heart rate, Systolic and Diastolic Blood Pressure and Perfusion Index were measured before induction of anesthesia, before intubation and one minute, three minutes, five minutes after the insertion of the endotracheal tube. Increase in heart rate by ?10 beats per minute, systolic and diastolic blood pressure by ?15 millimeters of mercury and decrease in Perfusion index ?10% after endotracheal intubation as compared to preintubationvalue were considered positive haemodynamic changes.Results: Endotracheal intubation produced a significant increase in heart rate and blood pressure whereas perfusion index decreased significantly. Our study showed that perfusion index response criterion achieved 97.7% (Confidence interval 97.58-97.86) sensitivity in detecting the stress response to insertion of endotracheal tube whereas systolic and diastolic blood pressure achieved sensitivity of 90% and 92% respectively.Conclusion: Perfusion Index is easier, reliable and non-invasive alternative to conventional haemodynamic criteria for detection of stress response to endotracheal intubation.